Discovery of Teneurins - Baumgartner, Stefan; Wides, Ron (Frontiers in Neuroscience, 2019)
Teneurins were first discovered and published in 1993 and 1994, in Drosophila melanogaster as Ten-a and Ten-m. They were initially described as cell surface proteins, and as pair-rule genes. Later, they proved to be type II transmembrane proteins, and not to be pair-rule genes. Ten-m might nonetheless have had an ancestral function in clock-based segmentation as a Ten-m oscillator. The turn of the millennium saw a watershed of vertebrate Teneurin discovery, which was soon complemented by Teneurin protein annotations from whole genome sequence publications. Teneurins encode proteins with essentially invariant domain order and size. The first years of Teneurin studies in many experimental systems led to key insights, and a unified picture, of Teneurin proteins.